2015
DOI: 10.3174/ajnr.a4528
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Pseudoprogression in Vertebral Bodies Treated with Stereotactic Radiosurgery: A Secondary Analysis of Prospective Phase I/II Clinical Trials

Abstract: Background and Purpose Osseous pseudoprogression (OPP) on MRI can mimic true progression in lesions treated with spine stereotactic radiosurgery (SSRS). Our aim is to describe the prevalence and time course of OPP, in order to assist radiologists in assessment of post-SSRS patients. Materials and Methods A secondary analysis of two prospective trials was performed. MRIs before and after SSRS were assessed for response. OPP was defined as transient growth in signal abnormality centered at the lesion with a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Symptoms or vertebral fractures at the time of tumour growth on imaging did not occur in any of the patients who were deemed to have PP. These findings are similar to the series by Amini et al, which demonstrated a PP rate of 14% and median time to occurrence of 5 months 26 . It is worth noting that the use of the 80% isodose line to describe the high dose region was extrapolated from the CNS setting and has not been validated for the spine.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Symptoms or vertebral fractures at the time of tumour growth on imaging did not occur in any of the patients who were deemed to have PP. These findings are similar to the series by Amini et al, which demonstrated a PP rate of 14% and median time to occurrence of 5 months 26 . It is worth noting that the use of the 80% isodose line to describe the high dose region was extrapolated from the CNS setting and has not been validated for the spine.…”
Section: Resultssupporting
confidence: 83%
“…However, for patients with spine metastases, unless there is cord compromise or vertebral instability, a conservative approach with serial imaging is usually adopted given the invasive nature and morbidity of surgery which may ultimately prove to be unnecessary. Earlier reports describing PP following spine SABR 26‐29 have recently been followed by two more recent publications. Bahig et al performed a retrospective quantitative analysis of 49 spinal lesions treated with SBRT 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an experienced neuroradiologist is imperative to assess whether changes seen on imaging are related to disease progression versus radiation-induced change, because osseous pseudoprogression has been reported and is an active area of investigation. 2 Similarly, for pain control, the lack of standardization in the pain assessment tool and time points at which response was determined are confounding factors. The SPIne response assessment in Neuro-Oncology (SPINO) group was formed to address such issues.…”
Section: Discussionmentioning
confidence: 99%
“…The association of single-fraction SBRT (versus multifraction) with greater pain flare rates, 13 and emerging evidence of early-onset pseudoprogression 14 are clinical surrogates confirming an early intense inflammatory reaction. Alternatively, we postulate that late-onset VCF is because of the slow induction of necrosis yielding damage to the vertebral body boney and cartilaginous structure that eventually compromises the capacity of the vertebral body to withstand the mechanical load, manifesting as VCF.…”
Section: Discussionmentioning
confidence: 99%